2023
DOI: 10.17268/sci.agropecu.2023.020
|View full text |Cite
|
Sign up to set email alerts
|

Botanical diversity, structure and composition in cocoa agroforest systems in Alta Verapaz, Guatemala

Abstract: The tree composition in cocoa agroforestry systems (CAFS) in Guatemala is valued for providing a number of ecosystem services. Despite the importance of the trees in these systems, little is known about the tree species richness and its contribution to the conservation of diversity. We studied the botanical composition of CAFS of different ages in the Alta Verapaz department of Guatemala. In total, 70 survey plots with a size of 2500 m2 were established. An inventory was carried out in each sampling unit, reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…On the other hand, it was found that the timber potential in Lanquín differs from that of the evaluated CAFS in other municipalities. This is due to the farmers' preference for fast-growing trees with less canopy coverage, which, in turn, have the capacity to provide shade and improve soil fertility (Matey et al, 2013;Villanueva-González et al, 2023).…”
Section: Total and Commercial Volume Of Timbermentioning
confidence: 99%
“…On the other hand, it was found that the timber potential in Lanquín differs from that of the evaluated CAFS in other municipalities. This is due to the farmers' preference for fast-growing trees with less canopy coverage, which, in turn, have the capacity to provide shade and improve soil fertility (Matey et al, 2013;Villanueva-González et al, 2023).…”
Section: Total and Commercial Volume Of Timbermentioning
confidence: 99%